2020
DOI: 10.5688/ajpe7682
|View full text |Cite
|
Sign up to set email alerts
|

Global Health Learning Outcomes by Country Location and Duration for International Experiences

Abstract: Objective. To determine the impact of country income classification and experience duration on learning outcomes for student pharmacists participating in international advanced pharmacy practice experiences (APPEs). Methods. A mixed-methods, longitudinal study evaluated 81 fourth-year student pharmacists participating in an international APPE through one of three US universities. A pre-post survey was administered to evaluate students' self-perceived growth across 13 competencies established by the Consortium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The GHELP model is an outcome of the original data analysis of two prior studies [ 14 , 15 ] that helps explain how students’ knowledge, skills, and attitudes progress over time while on global health experiences. This progression model has three constructs (cultural awareness, appreciation and sensitivity) and incorporates learning from external and internal influences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GHELP model is an outcome of the original data analysis of two prior studies [ 14 , 15 ] that helps explain how students’ knowledge, skills, and attitudes progress over time while on global health experiences. This progression model has three constructs (cultural awareness, appreciation and sensitivity) and incorporates learning from external and internal influences.…”
Section: Discussionmentioning
confidence: 99%
“…While the objective of two prior studies of this research was to determine what students learned while abroad on international APPEs, discussion with the research team and analysis of the analytic memos from the coding process revealed new questions as to how students learned these outcomes while abroad [ 14 , 15 ]. Utilizing the aforementioned codebook ( Supplementary Materials ), the researchers went back to the original open response survey and focus group data and analyzed these through the lens of Mezirow’s Transformative Learning Theory and Kolb’s Experiential Learning Theory to examine the connectivity between codes as students progressed on their international APPE [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, graduates from low-to middle-income countries showed enhanced cultural awareness, making them more empathetic and better practitioners. 45 Additionally, our survey explored the association between demographics and the self-assessed competency performance of graduates, showing that self-declared competencies differed by gender and age (graduation period). Many studies around the globe have shown that scores on competency evaluation in pharmacy schools differed by gender, age, race/ethnicity, and other factors.…”
Section: 41mentioning
confidence: 99%
“…Although many examples of interprofessional global health experiences have been described in the literature, only a few studies have specifically examined the impact of these experiences on learners' interprofessional attitudes. 7,10,11 These limited findings have indicated an overall positive impact on interprofessional attitudes, yet it is unclear which aspects of international experiences most contributed to learning and how this can be applied to enhance other interprofessional education (IPE) experiences. As health science training programs continue to focus on designing effective IPE curricula, we wanted to better understand how and why 2 our institution's global health experience impacted interprofessional learning.…”
Section: Introductionmentioning
confidence: 99%